Phage therapy of wound-associated infections - Zyman, Anna; Górski, Andrzej; Międzybrodzki, Ryszard (Folia microbiologica, 2022)
Phages are viruses which can specifically infect bacteria, resulting in their destruction. Bacterial infections are a common complication of wound healing, and experimental evidence from animal models demonstrates promising potential for phage-dependent eradication of wound-associated infections. The studies discussed suggest that phage therapy may be an effective treatment, with important advantages over some current antibacterial treatments. Phage cocktails, as well as co-administration of phages and antibiotics, have been reported to minimise bacterial resistance. Further, phage-antibiotic synergism has been reported in some studies. The ideal dose of phages is still subject to debate, with evidence for both high and low doses to yield therapeutic effects. Novel delivery methods, such as hydrogels, are being explored for their advantages in topical wound healing. There are more and more Good Manufacturing Practice facilities dedicated to manufacturing phage products and phage therapy units across the world, showing the changing perception of phages which is occurring. However, further research is needed to secure the place of phages in modern medicine, with some scientists calling upon the World Health Organisation to help promote phage therapy.
Keywords: bakteriální infekce; fágová terapie; bakteriofágy; zvířata; Anti-Bacterial Agents; Bacteriophages; Bacteria; Phage Therapy; Bacterial Infections; antibakteriální látky; Animals